2018
DOI: 10.15809/irriga.2018v23n1p168
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade E Tolerância Do Feijão Caupi Ao Estresse Salino

Abstract: PRODUTIVIDADE E TOLERÂNCIA DO FEIJÃO CAUPI AO ESTRESSE SALINO  CRISTIANO TAGLIAFERRE1; DIOGO ULISSES GOMES GUIMARÃES2; LORENA JÚLIO GONÇALVES3; CARLOS HENRIQUES FARIAS AMORIM1; SYLVANA NAOMI MATSUMOTO4 E LUCIALDO OLIVEIRA D’ARÊDE5 1Departamento de Engenharia Agrícola e Solos da Universidade Estadual Sudoeste da Bahia (UESB); Estrada do Bem Querer, km 04, Caixa Postal 95; CEP 45031-900, Vitória da Conquista – BA, tagliaferre@yahoo.com.br;2Rua José do patrocínio, 267, Alto maron, Vitória da Conquista-BA, diogoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…This denotes that the formation and development of the peanut grains were compromised by the increases in salinity of the irrigation water. Production losses caused by increases in salinity were also found by Correia et al (2009) for peanut plants of the cultivar BR-1, and by Tagliaferre et al (2018) for cowpea plants. The use of the pulse irrigation method resulted in a grain fresh weight 25.3% higher than the use of continuous irrigation.…”
Section: Results E Discussionsupporting
confidence: 70%
“…This denotes that the formation and development of the peanut grains were compromised by the increases in salinity of the irrigation water. Production losses caused by increases in salinity were also found by Correia et al (2009) for peanut plants of the cultivar BR-1, and by Tagliaferre et al (2018) for cowpea plants. The use of the pulse irrigation method resulted in a grain fresh weight 25.3% higher than the use of continuous irrigation.…”
Section: Results E Discussionsupporting
confidence: 70%
“…Sá et al (2018) found morphophysiological changes in cowpea plants, with reduction in their photosynthetic rate, due to stomatal restrictions and damage to the photosynthetic apparatus. Thus, the production of photoassimilates directly infl uences the production performance of cowpea (TAGLIAFERRE et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Oliveira et al (2015) found that the production of pods per cowpea plant under salt stress was reduced by 50% and that the number of seeds per pod (NSPO) decreased by 1.5 seeds per pod, for each unit increase in the electrical conductivity of irrigation water. According to Tagliaferre et al (2018), each unit increase in the electrical conductivity of irrigation water above the salinity threshold (3.3 dS m -1 ) lead to reductions of up to 25% in grain yield. Despite that, there is divergence in the reduction of cowpea production as a function of salt stress, caused by the different degrees of tolerance between varieties (DANTAS et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…For Tagliaferre et al (2018), crops such as beans and onions cannot be grown in areas with saline problems, with their resistance being 1 and 1.2 dS m -1 respectively. Already for Granja et al (2019), although salinity reduces the vegetative growth and productivity of cowpea, it did not influence the qualitative aspects of fruits and seeds, causing a slight increase in the harvest index.…”
Section: Resultsmentioning
confidence: 99%
“…Soils with high clay content have a damaged structure and reduced natural porosity, reflected in the decrease in drainage and plant growth, in addition to making it difficult to leach salts present in the profile (PEDROTTI et al, 2015). For Tagliaferre et al (2018), the harm caused by salinity to plants is associated with the reduction of the osmotic potential of the soil solution, nutritional disorders, particular effects of ions or the combination of these factors.…”
Section: Introductionmentioning
confidence: 99%